EFFECT OF SOME AUSTRALIAN NATIVE SHRUBS ESSENTIAL OILS ON IN VITRO RUMEN MICROBIAL FERMENTATION OF A HIGH-CONCENTRATE DIET - H. Jahani-Azizabadi2; Z. Durmic; J. Vadhanabhuti; P. E Vercoe (Journal of Animal and Plant Sciences, 2019)
The aim of the present study was to investigate the dose-response effect of selected Australian EOs on in vitro rumen fermentation characteristics in order to find a combination of EO and dose that may be effective against methane and ammonia-N, while maintaining rumen fermentation. Selected EO treatments significantly (P<0.05) reduced methane (between 25% and 97% reduction) and ammonia-N (between 19% to 70% reduction) concentrations when compared to control, and change occurred in a dose-dependent manner. However, other fermentation parameters were also reduced in all of these, but in Santalum spicatum EO treatment the effect on methane (50% reduction) and ammonia-N (59%reduction) were greater than the effect on overall fermentation (i.e. VFA reduced only up to 20%). Results of the present study demonstrated that at doses tested, it was not possible to dissociate the effects of EOs on in vitro fermentation, except in S. spicatum EO, where selected doses may reduce methane and ammonia N with less negative effect on overall fermentation by rumen microbes.
Keywords: essential oils; methane; ammonia-N; rumen fermentation; in vitro.